2018
DOI: 10.1002/brb3.1065
|View full text |Cite
|
Sign up to set email alerts
|

Vasogenic cerebral edema associated with the disability in activities of daily living in patients with chronic obstructive pulmonary disease

Abstract: IntroductionThe aim of this study was to explore whether patients with chronic obstructive pulmonary disease (COPD) develop vasogenic cerebral edema, and whether this edema contributes to the COPD‐related disability.MethodsEighteen stable patients with COPD and 17 matched healthy volunteers were enrolled. Apparent diffusion coefficient (ADC) values were calculated by voxel‐based analysis using DTI‐Studio software based on diffusion tensor imaging. COPD‐related disability was calculated using activities of dail… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
3
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 45 publications
1
3
0
Order By: Relevance
“…In addition, a neuroimaging study showed that corpus callosum integrity is correlated with iSP duration (Fling et al 2013). Therefore, our findings support a functional alteration in the bilateral connectivity in COPD patients and are thus consistent with previous findings of an abnormality in the corpus callosum structure of these patients (Wang et al 2018;Lee et al 2019;Yin et al 2019).…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…In addition, a neuroimaging study showed that corpus callosum integrity is correlated with iSP duration (Fling et al 2013). Therefore, our findings support a functional alteration in the bilateral connectivity in COPD patients and are thus consistent with previous findings of an abnormality in the corpus callosum structure of these patients (Wang et al 2018;Lee et al 2019;Yin et al 2019).…”
Section: Discussionsupporting
confidence: 92%
“…Therefore, our findings support a functional alteration in the bilateral connectivity in COPD patients and are thus consistent with previous findings of an abnormality in the corpus callosum structure of these patients (Wang et al . 2018; Lee et al . 2019; Yin et al .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations